NEEDS ANALYSIS OF ENGLISH FOR SPECIFIC PURPOSE FOR SHARIA BUSINESS MANAGEMENT STUDENTS - Lia Agustina Damanik (Institut Pendidikan Tapanuli Selatan, 2020)
This development research is specifically carried out in order to compile an English learning material for students of Sharia Business Management study program, but focus on the conventional economic terminologies. The research method used is the adoption of product development steps by Sugiyono. Analysis of two aspects, namely target needs and learning needs, was developed into a research instrument in the form of a questionnaire to measure listening, speaking, reading, and writing skills. The results of the data analysis indicate that in the preparation of a language development learning material, it is necessary to emphasize direct practice of the ability to use foreign language skills (listening, speaking, reading, and writing). In addition, Cooperative Learning is considered the most effective method.